Assessment of aboveground biomass and carbon accumulation at the carbon landfill sites of the Chechen state university named after A.A. Kadyrov on the territory of the city of Grozny - Iriskhanova Z.I.; Bekmurzayeva R.H. (BIO Web of Conferences, 2024)
Carbon exists as carbon dioxide in the atmosphere and makes up about 0.04% of the atmosphere. In the recent past, it has attracted a lot of attention as a greenhouse gas because it can affect the world climate model. Anthropogenic activities such as industrialization, deforestation, forest degradation and the burning of fossil fuels have caused an increase in atmospheric carbon levels and disrupted the global carbon cycle. The climate change expert group has identified five carbon pools of the terrestrial ecosystem that include biomass, namely aboveground biomass, underground biomass, debris, woody debris, and soil organic matter. Among all carbon pools, aboveground biomass makes up the bulk of the carbon pool.